Tropical Pacific cold tongue mode triggered by enhanced warm pool convection due to global warming - Ning Jiang; Congwen Zhu (Environmental Research Letters, 2020)
A cold tongue mode (CTM) formed in the 1980s as a La Niña-like stepwise response to recent global warming; however, a consensus has not been reached on the mechanism underlying the CTM formation. Here, we attribute the CTM to the enhanced deep convection of the warm pool regions over the western Pacific and south of North America. Increases in the sea surface temperatures in the two Pacific warm pool regions that occurred due to global warming exceeded the threshold of deep convection after the 1980s, which resulted in two opposite anomalous vertical circular circulation patterns and induced the CTM via the intensification, contraction, and westward shift of the Walker circulation and the uplift of the thermocline. Our results provide a novel explanation of the La Niña-like response under recent global warming.